Modified Sinc-Galerkin Method for Nonlinear Boundary Value Problems. (10th October 2012) - Hajji, M. A.; Al-Mdallal, Q. M.
Abstract : This paper presents a modified Galerkin method based on sinc basis functions to numerically solve nonlinear boundary value problems. The modifications allow for the accurate approximation of the solution with accurate derivatives at the endpoints. The algorithm is applied to well-known problems: Bratu and Thomas-Fermi problems. Numerical results demonstrate the clear advantage of the suggested modifications in obtaining accurate numerical solutions as well as accurate derivatives at the endpoints.